A probabilistic description of the bed load sediment flux: 2. Particle activity and motions - Roseberry, John C.; Schmeeckle, Mark W.; Furbish, David Jon (Journal of Geophysical Research: Earth Surface, 2012)
High‐speed imaging of coarse sand particles transported as bed load over a planar bed reveals that the particle activity, the solid volume of particles in motion per unit streambed area, fluctuates as particles respond to near‐bed fluid turbulence while simultaneously interacting with the bed. The relative magnitude of these fluctuations systematically varies with the size of the sampling area. The particle activity within a specified sampling area is distributed in a manner that is consistent with the existence of an ensemble of configurations of particle positions wherein certain configurations are preferentially selected or excluded by the turbulence structure, manifest as patchiness of active particles. The particle activity increases with increasing bed stress far faster than does the average particle velocity, so changes in the transport rate with changing stress are dominated by changes in the activity, not velocity. The probability density functions of the streamwise and cross‐stream particle velocities are exponential‐like and lack heavy tails. Plots of the mean squared particle displacement versus time may ostensibly indicate non‐Fickian diffusive behavior while actually reflecting effects of correlated random walks associated with intrinsic periodicities in particle motions, not anomalous diffusion. The probability density functions of the particle hop distance (start‐to‐stop) and the associated travel time are gamma‐like, which provides the empirical basis for showing that particle disentrainment rates vary with hop distance and travel time. Key Points Bed load particle activity systematically varies with scale Active particle configurations are preferentially selected by turbulence Particle velocities possess an exponential‐like distribution